TINJAUAN KONDISI FISIK ATLET WUSHU KABUPATEN KERINCI - Edwarsyah Edwarsyah; Istighfar Oradia Linas (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
The problem in this study was the athletes’s failureinthe game due to tiredness, even though the game time has not run out. Furthermore, in competing, Wushu athletes often lose speed in attacking or defending, the body was less agile to dodge and even punches, kicks and kickbacks were less powerful and not so hard.The type of the research was descriptive research. The population were all Wushu Athletes in Kerinci Regency in 2018. 15 samples were chosen. The sampling technique was done through